2018
DOI: 10.1002/syn.22082
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of diabetes mellitus on neuronal connectivity in limbic regions

Abstract: Diabetes mellitus (DM) is characterized by high levels of blood glucose. In recent years, its prevalence has increased, which was 422 million in the world in 2014. In elderly patients, DM is associated with deficits in memory and learning processes. The cognitive deficits lead to dementia. With the development of animal models in DM, it has been possible to better understand quantitative morphological changes in numerous neuronal structures belonging to the limbic system, such as the prefrontal cortex (PFC), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 75 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…At nanomolar concentrations, S100B has been indicated to have neurotrophic activity [24]. Previous studies have shown that the hippocampus is an important cognitive region of the brain, and cognitive dysfunction in diseases such as DM and AD has been found to be related to the hippocampus [27,28]. Nanomolar concentrations of S100B can promote hippocampal progenitor cell proliferation, neuronal differentiation and cognitive recovery [26].…”
Section: Discussionmentioning
confidence: 99%
“…At nanomolar concentrations, S100B has been indicated to have neurotrophic activity [24]. Previous studies have shown that the hippocampus is an important cognitive region of the brain, and cognitive dysfunction in diseases such as DM and AD has been found to be related to the hippocampus [27,28]. Nanomolar concentrations of S100B can promote hippocampal progenitor cell proliferation, neuronal differentiation and cognitive recovery [26].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that spine maturation, synaptic plasticity, and neuronal connectivity are reduced in metabolic imbalance conditions such as diabetes and obesity 60 , we assumed that exendin-4 may recover the neural structure and synaptic plasticity in the obese brain. Therefore, GLP-1 may be vital to the treatment of the diverse neuropathology caused by metabolic imbalance.…”
Section: Furthermore the Reduction Of Gsk-3β Activation Results In Tmentioning
confidence: 99%
“…The correlation between NfL and other biochemical parameter was unable to be made. The possible explanation might be the multiple comorbidities in ESRD patients, such as unmeasured uremic toxin contributing to neuroinflammation within the glial cells (Adesso et al, 2017) or the hyperglycemic status disturbing morphology of neuronal structure (Flores-Gómez et al, 2019). The higher percentage of diabetes mellitus in cognitive impairment group might influence the performance of NfL.…”
Section: The Role Of Nfl For Risk Assessment For Cognitive Impairmentmentioning
confidence: 99%